Pengaruh Program Literasi Sekolah Terhadap Keterampilan Membaca Teks Ulasan Pada Peserta Didik Kelas VIII SMP N 1 Botupingge Tahun 2023/2024: Penelitian - Sune, Sandrawati; Supriyadi; Salam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The study aimed to determine whether there is an influence o the school literacy program on the review text reading skilsso grade VIII students at SMP N 1 Botupingge in the 2023/2024 academic year, as well as to determine the inhibiting factors and supporting factors o the school literacy program on the review teks reading skiils of grade VIII students at SMP N 1 Botupinggein the 2023/2024 academic year. This study used a quantitative method and a pretest-posttest control group design. The result s o the study show that score of tcount > ttable or 2,082 > 1,677 then H0 rejected this mean that Ha is accepted thus, it can be concluded that there is a signiicant positive influence on student‘ review text reading skiil using the literacy program, which is higher compared to using conventional methods. The supporting factors or the implementasion of the literacy program include the availability of appropriate materials, while the inhibiting actors include time constraints, lack o book collection and lowreading interest.